Outstanding books for the college bound : titles and programs for a new generation - Carstensen, Angela; Young Adult Library Services Association (Chicago : American Library Association, 2011)
Connecting teens to books they'll truly enjoy is the aim of every young adult librarian, and the completely revamped guide Outstanding Books for the College Bound will give teen services staff the leg up they need to make it happen. Listing nearly 200 books deemed outstanding for the college bound by the Young Adult Library Services Association (YALSA), this indispensable resource Examines how the previous lists in the series were developed, and explains the book's new layout Features engaging, helpful book descriptions useful for readers' advisory Offers programming tips and other ideas for ways the lists can be used at schools and public libraries Includes indexes searchable by topic, year, title, and author More than simply a vital collection development tool, this book can help librarians help young adults grow into the kind of independent readers and thinkers who will flourish at college.
pt. 1. Developing and using the lists -- pt. 2. The annotations, revised and expanded by Angela Carstensen.
"A YALSA publication."
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: College students -- Books and reading -- United States; Youth -- Books and reading -- United States; Young adults' libraries -- United States -- Book lists; Young adults' libraries -- Activity programs -- United States; Best books -- United States; Étudiants -- Livres et lecture -- États-Unis.; Jeunesse -- Livres et lecture -- États-Unis.; Bibliothèques pour la jeunesse -- Activités -- États-Unis.; Meilleurs ouvrages -- États-Unis.; LITERARY CRITICISM -- Books & Reading; Best books; College students -- Books and reading; Young adults' libraries; Young adults' libraries -- Activity programs; Youth -- Books and reading; United States; Electronic books; Bibliographies